2020
DOI: 10.3390/nu12051269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Ketogenic Diet Containing Medium-Chain Triglycerides and Endurance Training on Metabolic Enzyme Adaptations in Rat Skeletal Muscle

Abstract: Long-term intake of a ketogenic diet enhances utilization of ketone bodies, a particularly energy-efficient substrate, during exercise. However, physiological adaptation to an extremely low-carbohydrate diet has been shown to upregulate pyruvate dehydrogenase kinase 4 (PDK4, a negative regulator of glycolytic flux) content in skeletal muscle, resulting in impaired high-intensity exercise capacity. This study aimed to examine the effects of a long-term ketogenic diet containing medium-chain triglycerides (MCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…But even with total elimination of dietary carbohydrate (e.g., fasting), the concentration of BOHB rises slowly, reaching steady state only after 2 to 3 wk ( 14 ). Further adaptations that may occur over weeks to months relate to the efficiency of BOHB transport into the brain ( 15 ), changes in muscle and liver metabolism ( 16–18 ), mitochondrial number and function ( 19 , 20 ) oxidative stress and inflammation ( 19–21 ), and hormonal responses ( 22 , 23 ). In time-course studies, negative nitrogen balance (indicative of lean mass loss) ( 24–26 ), fatigue ( 27 ), increased hunger ( 28 ), and decreased exercise tolerance ( 18 ) are characteristically observed with initiation of a ketogenic diet, but these adverse responses typically resolve after a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…But even with total elimination of dietary carbohydrate (e.g., fasting), the concentration of BOHB rises slowly, reaching steady state only after 2 to 3 wk ( 14 ). Further adaptations that may occur over weeks to months relate to the efficiency of BOHB transport into the brain ( 15 ), changes in muscle and liver metabolism ( 16–18 ), mitochondrial number and function ( 19 , 20 ) oxidative stress and inflammation ( 19–21 ), and hormonal responses ( 22 , 23 ). In time-course studies, negative nitrogen balance (indicative of lean mass loss) ( 24–26 ), fatigue ( 27 ), increased hunger ( 28 ), and decreased exercise tolerance ( 18 ) are characteristically observed with initiation of a ketogenic diet, but these adverse responses typically resolve after a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a sustained hemolysis over time, as a consequence of the progression of the disease, is able to saturate the buffering mechanisms of fr-Hb by Hp, which would induce a decrease in its levels, facilitating even more free Hb entry to the CNS through the damaged BBHE [ 38 ], as well as greater muscle destruction. Therefore, the fact that Hp levels, after 4 months of treatment, have not decreased but remain, whereas muscle percentages are increased significantly, could be associated with an improvement in muscular activity, possibly as a consequence of the anabolic effect at a muscular level (both from EGCG [ 21 ] and the increase of BHB prompted by the intake of coconut oil [ 27 ]), being that our hypothesis is that this improvement could be mediated in turn by the neutralization of free HB. As a consequence, this pattern in the secretion of the protein could be associated with its anti-inflammatory effect, as has already been observed in other diseases, as it promotes Hb–Hp binding, thereby inhibiting Hb-stimulated lipid peroxidation and reducing oxidation [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This would explain its neuroprotective activity against strokes and neurodegenerative diseases [ 25 ]. Additionally, there is evidence on the impact of ketosis, obtained through nutritional diets on anthropometric parameters, leading to a decrease in fat [ 26 ] and being associated with a greater activity of skeletal muscle as a result of the improved energetic performance in the muscles [ 27 ]. This evidence shows that ketogenic diets are used to improve neuromuscular diseases that need to mainly restore skeletal muscle [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous human study has reported an increase in blood triglycerides and an increase in RER during exercise after the 2-week MCTs ingestion [ 34 ], indicating that MCTs intake may promote both carbohydrate assimilation and oxidation. Furthermore, studies using animals have reported inhibition of the increase in pyruvate dehydrogenase kinase 4 protein, which suppressed the glycolytic system on a ketogenic MCTs diet [ 36 ] and increased blood glucose uptake on a high-fat MCTs diet [ 37 ]. The increase in carbohydrate oxidation obtained in the women in the present study may have been due not only to the increase in oxygen uptake by continuous MCTs ingestion but also to the enhancement of glucose metabolism shown in previous studies.…”
Section: Discussionmentioning
confidence: 99%